Impact of Cardiac Progenitor Cells on Heart Failure and Survival in Single Ventricle Congenital Heart Disease. Issue 7 (30th March 2018) - Sano, Toshikazu; Ousaka, Daiki; Goto, Takuya; Ishigami, Shuta; Hirai, Kenta; Kasahara, Shingo; Ohtsuki, Shinichi; Sano, Shunji; Oh, Hidemasa
Abstract : Rationale: : Intracoronary administration of cardiosphere-derived cells (CDCs) in patients with single ventricles resulted in a short-term improvement in cardiac function. Objective: : To test the hypothesis that CDC infusion is associated with improved cardiac function and reduced mortality in patients with heart failure. Methods and Results: : We evaluated the effectiveness of CDCs using an integrated cohort study in 101 patients with single ventricles, including 41 patients who received CDC infusion and 60 controls treated with staged palliation alone. Heart failure with preserved ejection fraction (EF) or reduced EF was stratified by the cardiac function after surgical reconstruction. The main outcome measure was to evaluate the magnitude of improvement in cardiac function and all-cause mortality at 2 years. Animal studies were conducted to clarify the underlying mechanisms of heart failure with preserved EF and heart failure with reduced EF phenotypes. At 2 years, CDC infusion increased ventricular function (stage 2: +8.4±10.0% versus +1.6±6.4%, P =0.03; stage 3: +7.9±7.5% versus −1.1±5.5%, P <0.001) compared with controls. In all available follow-up data, survival did not differ between the 2 groups (log-rank P =0.225), whereas overall patients treated by CDCs had lower incidences of late failure ( P =0.022), adverse events ( P =0.013), and catheter intervention ( P =0.005) compared with controls. CDC infusion was associated with a lower risk of adverse events (hazard ratio, 0.411; 95% CI, 0.179–0.942; P =0.036). Notably, CDC infusion reduced mortality ( P =0.038) and late complications ( P <0.05) in patients with heart failure with reduced EF but not with heart failure with preserved EF. CDC-treated rats significantly reversed myocardial fibrosis with differential collagen deposition and inflammatory responses between the heart failure phenotypes. Conclusions: : CDC administration in patients with single ventricles showed favorable effects on ventricular function and was associated with reduced late complications except for all-cause mortality after staged procedures. Patients with heart failure with reduced EF but not heart failure with preserved EF treated by CDCs resulted in significant improvement in clinical outcome. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifiers: NCT01273857 and NCT01829750. Abstract : Supplemental Digital Content is available in the text.